Indonesia and World Maritime Axis Vision: A Geo-Economics Review - Barata, Fausta Ari (Archives of Business Research, 2020)
To increasing Indonesia marine, President Joko Widodo has idea and planning not only increasing marine resources, and fishery is the world maritime axis. But also infrastructure development of marine to pointed out to develop the country from geo-economics review. There are main pillars as the foundation of vision on Indonesia’s marine development. There are policies, marine development, and fishery with activity program 100 days which produce fisherman improvement, and marine resources.